Comparison of video-assisted thoracic surgery with open surgery in the treatment of ectopic mediastinal parathyroid tumors - Du, Hailei; Shi, Minmin; Zhu, Lianggang; Che, Jiamin; Hang, Junbiao; Chen, Zhongyuan; Li, Hecheng (Journal of Thoracic Disease, 2017)
Background: To investigate the therapeutic effect of different surgical treatment for ectopic mediastinal parathyroid tumors and pathological features. Methods: A total of 21 patients who were diagnosed with ectopic mediastinal parathyroid tumors and underwent surgeries in our department from May 1995 to May 2015 were collected and retrospectively analyzed. Results: Twenty-one patients including 8 female (36.4%) and 13 male (63.6%) were collected. Among these patients, 9 cases were treated with video-assisted thoracic surgery (VATS), while 13 cases were treated with open surgery (including one secondary open operation after thoracoscopic operation). The average size of mediastinal tumors was 2.17±1.22 cm. For the post-operational pathology, 16 cases (76.2%) were diagnosed as ectopic parathyroid adenoma; 4 cases (19.0%) were diagnosed as parathyroid hyperplasia, while only 1 case (4.8%) was diagnosed as parathyroid adenocarcinoma. Conclusions: Parathyroid adenoma accounts for the major pathological type of ectopic mediastinal parathyroid tumors. In addition, the correct diagnosis with precise preoperative location was the key for the treatment of ectopic mediastinal parathyroid tumors accompanied with hyperparathyroidism. Surgical intervention was demonstrated to be an effective way for the treatment of ectopic mediastinal parathyroid tumors with satisfied therapeutic outcome, especially for the VATS due to its unique clinical advantages. However, there may some difficulties when locating ectopic mediastinal parathyroid tumor less than 1 cm and the operators should be very cautious when performing thoracoscopic operations.